Estudio social y jurídico respecto del consumo de sustancias sujetas a fiscalización en los menores de edad, y soluciones para la salud - Jiménez González, Filiberto Patricio (2016)
In this research, I intend to inform readers that the topic "Social and Legal Study respect Consumption Subjected substances under control in the minors, and solutions for Health" is highly relevant study because that drug use is a serious social problem in children and adolescents should be analyzed carefully in its structure and size. The Constitution of the Republic of Ecuador as supreme law guarantees the right of children and adolescents, through the State who must take measures to prevent the use of narcotic drugs or psychotropic substances and consumption of alcohol and other harmful substances health and development; therefore considers addiction a public health and must provide treatment and rehabilitation to occasional, regular and problem users. This in coordination with the Code for Children and Adolescents, which guarantees children and adolescents the right to enjoy the highest level of physical, mental, psychological and sexual health., Allowing unlimited and uninterrupted access to health services public, for the prevention, treatment of illness and rehabilitation of health, indicating that public services are free for children and adolescents in need; however the reality is different because it is observed under immersed age problems of addictions to drug and can not receive treatment because there are no therapeutic clinical public couple who provide care to children, which violates the right to health and personal integrity of a minor.The theoretical, legal and doctrinaire gathering, conducting surveys and interviews yielded criteria well known clear and precise fundamentals, literature, which contributed to the verification of the objectives and the testing of the hypothesis concerning this practice; both the Constitution of the Republic of Ecuador, as the Code of Children and Adolescents and the Organic Law of Health, to ensure the health of a minor, however not created Medical Centers that provide proper care and free timely treatment